A scoping review of end user involvement in disability research. Issue 2 (April 2016) - Joss, Nerida; Cooklin, Amanda; Oldenburg, Brian
Abstract: Background: Involving clients and consumers of health care in research, policy and health service development has been widely advocated for across a number of different fields and disciplines. Despite some promising evidence, 'end users' have not been meaningfully involved in all stages of the research process in the area of disability research. Objective: To conduct a scoping review on end user involvement in disability research, service and policy development. Methods: Literature was searched using electronic databases, hand searching reference lists of papers and grey literature. Electronic databases searched included the Cochrane Database of Systematic Reviews, MEDLINE, EMBASE, CINAHL, PsycINFO and Google Scholar. The search was restricted to articles published in English between January 2000 and April 2013. Results: Two clear themes emerged from a review of twenty-seven articles. Firstly, end users can benefit research as 'experts of experience' through their role as a co-researcher. Secondly, evidence suggests end users add value at different stages of the research process in this role. However, less is understood about end user involvement in the latter stages of the research process. Conclusions: This review suggests that end users can meaningfully contribute to the quality of disability research. End users are likely to engage in research with differing perspectives, desires to be involved at distinct stages of the process, differing roles and different abilities to participate in the research. Academic rigor, however, must be maintained by the researcher.